THE IMPLEMENTATION OF ERP IN AN INDUSTRIAL COMPANY ENCOUNTERED PROBLEMS AND SOLUTIONS - Erdil, Aysenur; Basligil, Huseyin (YILDIZ TECHNICAL UNIV, 2011)
Advanced Information Technologies has become an indispensable part of organizations in Today's dynamic and competitive business enviroment. In a highly dynamic and competitive business context, the emerge of new information technologies has become a rapid process. One of new Information technologies is Enterprise Resource Planning(ERP). Especially, the last ten years have seen a dramatic growth in the word-wide use of ERP sytems. ERP Systems, by integrating every single functional unit of an organization into a single common computer-based system, creates a new process-oriented business model that is required in order for a business to remain competitive in today's unstable business enviroment. This study with the help of a questionnaire has examined operation of Enterprise Resource Planning (ERP) which is a modular software package implementing all the enterprise functionality through an integrated data system. All the problems and issues encountered have been investigated thoroughly with the questionnaire after ERP package on-site setup. In addition, modules which caused the most frequent problems have been studied. Moreover, employed methods to resolve the issues that enterprise has experienced and reasons to those problems have been investigated. In order to reduce complexity of implementations of ERP, importance of implementation factors and implementation problems in multinational companies' ERP implementation were examined in this study. In order to clarify these problems and national factors' effect on them, ERP implementation at fifteen companies were examined through an ERP questionnaire. Subsequently, national implementation factors' effect on the implementation problems were investigated through statistical studies on SPSS software. Understanding these effects, problems and their solutions will enable multinational companies more proactive in their ERP implementations.
Keywords: Enterprise resource planning; enterprise resource planning problems; in the implemention of ERP industrial company encountered problems and solutions; Engineering